2014
DOI: 10.21608/eajbsa.2014.13138
|View full text |Cite
|
Sign up to set email alerts
|

Biological studies on Bracon brevicornis (Hymenoptera: Braconidae) reared on different host larvae

Abstract: The present work was carried out to study the biological aspect of B. brevicornis when reared on different hosts (Ephestia kuehniella, Galleria mellonella, Corcera cephalonica, Sesamia cretica, Spodoptera littoralis and Pectinophora gossypiella). Our Results assured that the type of host had great impact on the durations of the immature stages and longevity of the parasitoid. The highest & lowest incubation periods were when reared the parasitoids on Pectinophora gossypiella (45.75±1.4hours) and E. kuehniella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…The findings of Ghimire and Phillips (2010) depict that B. hebetor did not lay eggs on all the host it parasitizes which reinforce the relevance of our findings. Our findings are concurrent with the findings of Bakr et al (2014) who reported that B. brevicornis preferred to oviposit on last instar larva compared to early instars. According to Kandil et al (2018) the total soluble proteins, carbohydrates, fats were present in larger quantities in bigger larvae or later instars compared to early instars, which is a key factor influencing the preference of later instars over early instars.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of Ghimire and Phillips (2010) depict that B. hebetor did not lay eggs on all the host it parasitizes which reinforce the relevance of our findings. Our findings are concurrent with the findings of Bakr et al (2014) who reported that B. brevicornis preferred to oviposit on last instar larva compared to early instars. According to Kandil et al (2018) the total soluble proteins, carbohydrates, fats were present in larger quantities in bigger larvae or later instars compared to early instars, which is a key factor influencing the preference of later instars over early instars.…”
Section: Resultssupporting
confidence: 92%
“…The longevity of adults emerged from different instars were found to be on par with each other and it ranged from 362.0 to 362.8 h. There was no significant difference between instars, with regard to developmental duration of B. brevicornis (Fig. 1) which is in line with the findings of Srinivasan and Chandrikamohan (2017) and Bakr et al (2014). In contrary, Kandil et al (2018) reported that the developmental duration was shorter on small sized hosts like Pectinophora gossypiella (Saunders) and Earias vitella (Fabricius), but longer on large sized hosts like Spodoptera littoralis (Boisduval) and Helicoverpa armigera (Hubner).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation